Syndrome of Primary Myocardial Hypertrophy: Clinical and Morphological, Genetic Diagnostics and Comparison of Sarcomerial Variants of Cardiomyopathy and its Phenocopy - O. V. Blagova; E. V. Zaklyazminskaya; E. A. Kogan; V. P. Sedov; G. М. Radzhabova; M. Е. Polyak; A. V. Nedostup (Рациональная фармакотерапия в кардиологии, 2019)
Aim. To study the nosological spectrum in the syndrome of primary left ventricle hypertrophy (PLVH) using morphological and genetic diagnostics and to compare the clinical course of true hypertrophic cardiomyopathy (HCM) and its phenocopy.Material and methods. Fifty five adult patients (29 men, 48.2±17.0 years) with PLVH (12 mm and more) were included. The exclusion criteria were athletic heart, hypertensive heart disease, severe valvular disease and other causes of secondary left ventricle (LV) hypertrophy. We performed 11 endomyocardial biopsy, 8 intraoperative biopsy, 1 study of explanted heart, 1 autopsy with virus investigation (real-time polymerase chain reaction) of the blood and myocardium. Mutational screening had included simultaneous sequencing of the MYBPC3, TAZ, TPM1, LDB3, MYL2, ACTC1, MYL3, MYH7, TNNI3 and TNNT2 genes based on NGS technology (Ion Torrent PGMTM) with following Sanger resequencing of potentially significant genetic variants. For patients with a phenotype of particular genetic syndrome the Sanger sequencing of target gene(s) for performed first. Clinical examination had included electrocardiography, Holter monitoring, echocardiography, coronary angiography, computer tomography/magnetic resonance imaging (by indication). The mean follow-up was 8 [3;32] month.Results. Isolated HCM was found in 28 patients, and 10 have a combination of HCM and noncompaction myocardium (NCM). Mutations in the MYH7 and MYBPC3 genes were detected in six cases. In 17 cases (30.9%) the non-sarcomeric causes of LVHS were detected. Three patients had Fabry disease, 2 ‒ had Danon disease, in 10patients we found amyloidoses, in 1 – Friedreich ataxia, and 1 patient was diagnosed with LEOPARD syndrome (all cases were confirmed by DNA diagnostics). Genotype-positive diagnosis was established in 23.6% of patients. In patients with HCM were significantly more frequent asymmetric septal hypertrophy with obstruction and muscle bridges, in other forms of primary hypertrophy – right ventricular hypertrophy, low QRS voltage, QS complexes and increasing of ejection fraction (EF) (55.7±12.5% vs 62.5±10.1% in HCM, p=0.08). The morphologic signs of myocarditis were in 46.7% of patients with HCM detected: in 3 patients with NCM and in 4 patients with isolated HCM. The viral genome in the myocardium was in 11 patients with HCM (73.3%) detected, previously human herpes virus type 6 (it was correlation with myocarditis) and parvovirus B19. Eleven patients died due to a stroke/heart failure without no significant differences between patients with HCM and phenocopy.Conclusion. The spectrum of causes of the primary left ventricular hypertrophy is very wide. The frequency of myocarditis associated with sarcomeric HCM was 46.7%. When lower EF and heart failure in patients with HCM can be result of myocarditis, in patients with storage disease they are the result of disease itself.